Characterization and robust nature of newly isolated oleaginous marine yeast Rhodosporidium spp. from coastal water of Northern China - Wang, Qiuzhen (AMB Express, 2017)
A total of ten marine yeast strains isolated from Bohai Sea, Northern China were identified to be members of three genera Rhodosporidium, Rhodotorula, and Cryptococcus. Two representative strains Rhodosporidium TJUWZ4 and Cryptococcus TJUWZA11 with high lipid content based on Nile red staining method were further characterized. A wide range of culture conditions (C and N sources, pH, temperature, salinity and C/N ratio) were tested to characterize the biomass and lipid production (yield and productivity) of these strains. Results indicated that Rhodosporidium TJUWZ4 was capable of achieving lipid yield up to 44% and 0.09 g/l–h productivity on glucose and peptone medium at pH 4, 20 °C, 30% salinity, and C/N 80. Three fatty acids, namely oleic acid (18:1), palmitic acid (C16:0) and linoleic acid (18:2) were the major intracellular fatty acids, which accounted for 90% of total lipids. With promising features for intracellular lipid accumulation, Rhodosporidium TJUWZ4 is a robust strain with great potentials for application in biodiesel production from renewable feedstocks. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13568-017-0329-x) contains supplementary material, which is available to authorized users.